Does intergenerational support affect older people's social participation? An empirical study of an older Chinese population - Yiqi Wangliu (Elsevier, 2023)
As a means of social support, intergenerational support plays an essential role in encouraging older people to participate in society. Data on 3142 older adults were collected from the China Survey of Elderly Health Influencing Factors (CLHLS), and logistic regression models were used to determine the effects of several types of intergenerational support on social participation and whether self-rated health and life satisfaction mediated the associations between intergenerational support and social participation. Among all the three types of intergenerational support, the results showed that financial support and emotional support were positively associated with the social participation of the older Chinese in our sample. We observed rural-urban differences in the effects of financial support and emotional support on social participation, which were significant in the urban groups. Gender differences also exist in these relationships. The effects of emotional support on social participation were significant in both groups and the impact of financial support was obvious only in the female group. Regarding the mediating effect, financial support was found to improve the participants' self-rated health, which enhanced their social participation. Emotional support increased the participants' life satisfaction, which led to higher levels of social participation. Based on the findings of this study, policymakers should advocate to strengthen financial and emotional support from adult children in the community.